Comprehensive Management of Septic Shock Secondary to Intra-Abdominal Infection Complicated by Acute Respiratory Distress Syndrome: A Case Report - Sahat , David; Kestriani , Nurita Dian; Ismandiya, Annisa Isfandiary (Journal of Society Medicine, 2026)
Introduction: Septic shock is a life-threatening complication frequently encountered after major abdominal surgery and is associated with substantial morbidity and mortality in the intensive care unit (ICU). Intra-abdominal infection following laparotomy is a common precipitating source of sepsis that may rapidly progress to circulatory failure. The development of acute respiratory distress syndrome (ARDS) further exacerbates disease severity and necessitates early recognition and coordinated multidisciplinary management. Case Description: We report the case of a 65-year-old man who developed septic shock secondary to postoperative peritonitis following a laparotomy. The patient had previously undergone low anterior resection for rectal carcinoma. On intensive care unit (ICU) admission, the patient presented with severe hemodynamic instability requiring aggressive fluid resuscitation, vasopressor support, and invasive mechanical ventilation. On ICU day three, the patient developed ARDS, characterized by persistent fever, marked leukocytosis, worsening hypoxemia, and bilateral pulmonary infiltrates on chest radiography. Management included early goal-directed resuscitation, vasopressor therapy, and empiric broad-spectrum antibiotics (meropenem and levofloxacin). Lung-protective ventilation strategies were implemented in close collaboration with intensivists, surgeons, and anesthesiologists. The patient showed gradual clinical improvement and was successfully extubated on ICU day ten. Conclusion: This case underscores the critical importance of rapid recognition and meticulous management of septic shock secondary to intra-abdominal infection complicated by ARDS. Optimal outcomes depend on timely resuscitation, appropriate empiric antimicrobial therapy, early identification of ARDS, implementation of lung-protective ventilation, and a coordinated multidisciplinary approach to critical care management.